Treatment program for ex-jailed sex offenders in Uruguay: from knowledge to policy. - Galeotti, Raquel; López-Gallego, Laura; López-Gómez, Alejandra (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2022)
In this article, we discuss the process of implementing a pilot program of the treatment of sex offenders in Uruguay. We implemented an intervention-research based on the case study method delimited in terms of institutional and thematic scenarios; a national public institution whose main objective is the socio-labor and community inclusion of formerly incarcerated people. The data collection took place between February and October 2018, through group interviews with the technical team of the program and semi-structured interviews with the directorate. We present the analyzed theoretical and technical dimensions involved in the implementation of a community-based program for sexual offenders, according to two analytical lines: the specificity of the approach towards sexual offenders and the conceptions of the key institutional actors surrounding sexual violence.